(untitled) (Eurasian Medical Research Periodical, 2025)
This article presents current data on the incidence, risk factors, and pathogenetic mechanisms of head and neck cancer (HNC). An analysis of the main predisposing factors is provided, including tobacco smoking , alcohol consumption, viral infection (in particular, human papillomavirus), and occupational and environmental exposures. Genetic and epigenetic features that contribute to epithelial malignancy are considered. Particular attention is paid to the role of lifestyle factors and early diagnosis of the disease. The results of a retrospective analysis of patients with squamous cell carcinoma of the head and neck are presented